2009
DOI: 10.1093/glycob/cwp095
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-glycosylation of the SEA module of rodent Muc3 in posttranslational processing of its carboxy-terminal domain

Abstract: A prominent feature of the rodent Muc3 SEA module is the precursor cleavage event that segregates the O-glycosylated N-terminal fragment and transmembrane domain into the noncovalently attached heterodimer. There are seven potential N-glycosylation sites that occur in a cluster in the SEA module of Muc3. However, it is unknown if these sites are modified or what the function of these N-glycans may be in the SEA module. Our data show that the proteolytic cleavage of the rodent Muc3 SEA module was partially prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These data suggest that the full length CRD1-L-CRD2 protein with an intact SEA domain are required for the protein to be fully functional. He, et al have shown that within the SEA module several N-glycosylation sites flanking the GSVVV cleavage site may control the extent of cleavage that occurs at this cleavage site, indicating the functional importance of the full SEA module [22]. Further experiments with site directed mutagenesis of the SEA cleavage site would be indicated to determine more specifically if this plays a role in recombinant mucin function, and also what part of the SEA module is important for functionality.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the full length CRD1-L-CRD2 protein with an intact SEA domain are required for the protein to be fully functional. He, et al have shown that within the SEA module several N-glycosylation sites flanking the GSVVV cleavage site may control the extent of cleavage that occurs at this cleavage site, indicating the functional importance of the full SEA module [22]. Further experiments with site directed mutagenesis of the SEA cleavage site would be indicated to determine more specifically if this plays a role in recombinant mucin function, and also what part of the SEA module is important for functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Residues other than those involved in the autoproteolysis were found to have an impact on the stabilization of the noncovalent subunit interaction 31 and on the level of N-glycosylation whose modifications disrupt mucin functions. 32 All TM mucins of interest exhibit the canonical SEA domain except MUC4. Nevertheless, as previously demonstrated, the DI located between EGF1 and EGF2 domains can be considered as a degenerate SEA-like domain.…”
Section: Physiological and Pathological Aspectsmentioning
confidence: 99%
“…However, inhibition of the cleavage potency of the SEA domain has abolished the whole function of the mucins regarding proliferation and migration. 32,33 There is also evidence of a second cleavage site in several mucins, 51,59 which would involve the release of a full soluble extracellular subunit and a free cytoplasmic subunit leading to transduction of the signal to the nucleus. 60 Another role for this SEA domain could be to form a ligand−receptor combination from a unique gene.…”
Section: Physiological and Pathological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations